n-alkane, fatty acid, and lignin phenol-based indices from sediment core PS51/154-11 - Tsai-Wen Lin; Tommaso Tesi; Jens Hefter; Hendrik Grotheer; Gesine Mollenhauer (PANGAEA, 2025)
This dataset includes biomarker indices and data used to calculate the mass accumulation rate of high molecular weight fatty acids in core PS51/154-11, including 1) n-alkane-based indices: the Carbon Preference Index (CPI) and the Sphagnum proxy (C25/(C25+C29) ratio); 2) lignin phenol-based indices: the syringyl phenols to vanillyl phenols ratio (S/V), the cinnamyl phenols to vanillyl phenols ratio (C/V), and the vanillic acid to vanillin ratio (Vd/Vl); 3) data for calculating the mass accumulation rate of high molecular weight fatty acids (C24:0+C26:0+C28:0+C30:0, HMW fatty acid MAR), which includes sedimentation rate, dry bulk density, and high molecular weight fatty acid content. N-alkanes and fatty acids were extracted with a mixture of dichloromethane (DCM) + methanol (v/v = 9:1) and analyzed with an Agilent 7890A gas chromatograph equipped with a flame ionization detector (GC-FID) using an Agilent J&W DB-5MS column (60 m exttimes 250 μm exttimes 0.25 μm-thick film). Lignin phenols were obtained through the CuO oxidation process, extracted with ethyl acetate, and analyzed with an Agilent Technologies 7820A gas chromatograph coupled with a 5977B MSD mass selective detector (GC-MS) equipped with a 30m exttimes 320 μm exttimes 0.25 μm-thick film column (Trajan SGE PB-1).
In: Lin, Tsai-Wen; Tesi, Tommaso; Hefter, Jens; Grotheer, Hendrik; Wollenburg, Jutta Erika; Mollenhauer, Gesine (2025): Bulk organic matter δ13C, biomarker, and microfossil radiocarbon data of cores PS51/154-11 and PS51/159-10 from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.980076